MicroRNA-622 is a novel mediator of tumorigenicity in melanoma by targeting Kirsten rat sarcoma - Dietrich, Peter; Kuphal, Silke; Spruss, Thilo; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2018)
The network of molecular players is similar when comparing neural crest-derived, actively migrating melanoblasts to melanoma cells. However, melanoblasts are sensitive to differentiation-initiating signals at their target site (epidermis), while melanoma cells maintain migratory and undifferentiated features. We aimed at identifying downregulated genes in melanoma that are particularly upregulated in melanoblasts. Loss of such genes could contribute to stabilization of a dedifferentiated, malignant phenotype in melanoma. We determined that microRNA-622 (miR-622) expression was strongly downregulated in melanoma cells and tissues compared to melanocytes and melanoblast-related cells. miR-622 expression correlated with survival of patients with melanoma. miR-622 re-expression inhibited clonogenicity, proliferation, and migration in melanoma. Inhibition of miR-622 in melanocytes induced enhanced migration. Kirsten rat sarcoma (KRAS) was identified as a major functional target of miR-622 in melanoma. We conclude that miR-622 is a novel tumor suppressor in melanoma and identify the miR-622-KRAS axis as potential therapeutic target.
EVALuna2:34069